Measures of Burnout and Empathy in United States Doctor of Pharmacy Students: Time for a Change?. (December 2022) - Jacoby, Jeanne L.; Cole, Jaclyn D.; Ruble, Melissa J.; Smith, Amy B.; Laubach, Lexis T.; Greenberg, Marna Rayl; Macfarlan, Jennifer E.; DeWaay, Deborah J.; Barraco, Robert D.; Shigo, Erin; Crowley, Lauren; Quinn, Joann Farrell
Purpose: To review interim data regarding longitudinal burnout and empathy levels in a single Doctor of Pharmacy class cohort. Methods: Students were emailed an electronic survey during their first semester and annually at the end of each academic year for a total of 3 years (2017-2020). Validated survey tools included the Jefferson Scale of Empathy (JSE) and the Maslach Burnout Inventory (MBI) student version. The JSE survey consists of 20 questions, with higher scores denoting more empathy. The MBI student version contains 3 subscales: exhaustion (higher scores are worse), cynicism (higher scores are worse) and professional efficacy (higher scores are better). Results: The median JSE score at the end of the third academic year (PY3) was 110, with females scoring significantly higher (114.5 vs. 103.5; p<0.02). A majority of the 62 students reported burn out (82.3%), scoring in the highest category for either exhaustion (76%) or cynicism (55%). A majority (66%) also reported a low or moderate professional efficacy score, a negative finding. Measures of student burnout increased after the start of the program and remained at the higher level each subsequent year (p<0.0001). In the Spring of 2020, during the COVID-19 pandemic, nearly every student had moderate or high levels of emotional exhaustion (97%) and cynicism (78%) as measured by the MBI. Conclusion: This interim data suggests high degrees of pharmacy student burnout. Empathy levels remained stable throughout the duration of the study. Pharmacy schools may need to focus on reform regarding well-being and prevention of burnout.